Metabolic Syndrome and 5-Year Incident Hyperuricemia Among Older Chinese Adults: A Community-Based Cohort Study - Liu JH (Dove Medical Press, 2020)
Jing-Hong Liu,1 Qing-Hua Ma,2 Yong Xu,1 Xing Chen,3 Chen-Wei Pan1 1School of Public Health, Medical College of Soochow University, Suzhou, People’s Republic of China; 2The 3rd People’s Hospital of Xiangcheng District, Suzhou, People’s Republic of China; 3Department of Children Health Care, Affiliated Suzhou Hospital of Nanjing Medical University, Suzhou, People’s Republic of ChinaCorrespondence: Xing ChenDepartment of Children Health Care, Affiliated Suzhou Hospital of Nanjing Medical University, No. 26 Dao Qian Road, Suzhou 215000, People’s Republic of ChinaTel +86 512 62362193Email cx1708@126.comChen-Wei PanSchool of Public Health, Medical College of Soochow University, 199 Ren Ai Road, Suzhou 215123, People’s Republic of ChinaTel +86 512 65883907Email pcwonly@gmail.comBackground: There was a lack of studies focusing on older adults about the longitudinal association between metabolic syndrome (MetS) and hyperuricemia (HUA). We aimed to assess the association of baseline MetS and incident HUA among older Chinese adults, with a special focus on the associations between different combinations of MetS components and HUA.Methods: Data of 3247 Chinese adults aged 60 years or older included in a community-based longitudinal cohort study were analyzed. Anthropometric examinations and collection of blood sample were conducted both at baseline and follow-up. HUA was defined as 7 mg/dl or above for men and 6 mg/dl or greater for women. MetS was assessed based on the National Cholesterol Education Program-Adult Treatment Panel III, and older adults with the presence of at least three of MetS components were considered as having MetS.Results: MetS and its components, including high blood pressure (BP), high body mass index, diabetes mellitus and high triglycerides, were significantly related to incident HUA. The association between high BP and incident HUA is strongest among the five MetS components. Among all combinations of MetS components, the group consisting of diabetes mellitus, high BP and high triglycerides had the highest odds for incident HUA (OR = 13.07, 95% CI = 4.95– 34.54).Conclusion: MetS and its components, except for low high-density lipoprotein cholesterol, could increase the risk of HUA among community-dwelling older adults, and high BP may be the most important determinant.Keywords: hyperuricemia, metabolic syndrome, older adults, epidemiology